2013
DOI: 10.1089/neu.2013.2955
|View full text |Cite
|
Sign up to set email alerts
|

Severe Traumatic Brain Injury in a High-Income Country: An Epidemiological Study

Abstract: This adult cohort determined the incidence and patients' short-term outcomes of severe traumatic brain injury (sTBI) in Switzerland and age-related differences. A prospective cohort study with a follow-up at 14 days was performed. Patients ≥16 years of age sustaining sTBI and admitted to 1 of 11 trauma centers were included. sTBI was defined by an Abbreviated Injury Scale of the head (HAIS) score >3. The centers participated from 6 months to 3 years. The results are presented as percentages, medians, and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 45 publications
2
57
0
1
Order By: Relevance
“…44 Fatality rates might also affect the occurrence of prolonged DOC. In-hospital fatality rate in the sTBI study at large was 29%, 26 of which 88% occurred within the first week, representing fatality rates in accordance with earlier reports 42,43,[45][46][47] and confirming high in-hospital fatality in the most severe injuries. 48 In accordance with this, only one patient with DOC died before the 12-month follow-up, tentatively confirming that patients with DOC who survive the first year postinjury can have a good chance of survival over the following years.…”
Section: Medical Complications and Interventionssupporting
confidence: 89%
See 1 more Smart Citation
“…44 Fatality rates might also affect the occurrence of prolonged DOC. In-hospital fatality rate in the sTBI study at large was 29%, 26 of which 88% occurred within the first week, representing fatality rates in accordance with earlier reports 42,43,[45][46][47] and confirming high in-hospital fatality in the most severe injuries. 48 In accordance with this, only one patient with DOC died before the 12-month follow-up, tentatively confirming that patients with DOC who survive the first year postinjury can have a good chance of survival over the following years.…”
Section: Medical Complications and Interventionssupporting
confidence: 89%
“…However, comparing their findings with the Norwegian numbers, the authors found that when sTBI was defined by a GCS score below 8, incidence numbers decreased to 5 per 100 000, in accordance with the Norwegian data. 42 Actually, the recent Swedish study of DOC incidence estimates 1.4 per 100 000 with sTBI in Sweden, suggesting even a lower occurrence than Norway and Switzerland. 18 However, within the 2-year sampling period of this study, the occurrence of DOC varied from 5 in 2009 to 2 in 2010.…”
Section: Medical Complications and Interventionsmentioning
confidence: 98%
“…This study is a part of the Swiss National Cohort of severe TBI entitled “Patient-relevant Endpoints after Brain Injury from Traumatic Accidents” (PEBITA; http://www.pebita.ch). Demographic data of this study has been published recently [24]. …”
Section: Methodsmentioning
confidence: 99%
“…Some early studies used ICD 8 (e.g., Engberg and Teasdale [1998]). 23 Other standardized coding schemes, such as the Abbreviated Injury Score for head injuries (AIS Head or HAIS) as in Walder and colleagues (2013), 24 and the Glasgow Coma Scale (GCS) as in Boto and colleagues (2009), 25 also were used occasionally. In summary, 31 studies used ICD (8th, 9 th , or 10th revision), and 20 studies used GCS or GCS and/or other criteria (usually AIS).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%